Marine nematodes from the coast line of the Gulf of Mexico. III. Additional species from Gulf Shores, Alabama. - Hopper, B. E. (Can. J. Zool., 1963)
Ten free-living marine nemas, including two new genera, seven new species, and a new subspecies, are recorded from the coast of Alabama (Halalaimus longisetosus n. sp., Pareurystomina acuminatum (de Man), Ditlevsenella filipjevi n. sp., Hypodontolaimus solivagus n. sp., Monoposthioides anonopsthia n. gen., n. sp., Anomonema haplostoma n. gen., n. sp., Axonolaimus paraponticus n. sp., Synodontium sansingi n. sp., Xyala striata Cobb, and Rhabditis bengalensis mexicana n. subsp.). Keys to the genera Ditlevsenella, Axonolaimus, and Synodontium are presented. A new genus, Synodontoides, is established for Axonolaimus procerus, which has characters intermediate between Axonolaimus and Synodontium. The nature and distribution of setae and hypodermal glands are discussed.
NeMys doc_id: 4557